THE ICEMAN COMETH AND THE HAIRY APE ARE THE FORMS OF METAPHORICAL EXPRESSIONS BY EUGENE O’NEILL’S VIEWS IN MODERN AMERICAN DRAMA - Ibrahim, Haider; Nawi, Abdullah Mohd; Ali, Ansam (International Journal of Psychosocial Rehabilitation, 2020)
This paper aims to study The Iceman Cometh and The Hairy Ape in metaphorical perspective. O’Neill wants to reveal metaphors in the selected plays. This metaphor leads to various expressions in modern American drama. The researchers use the qualitative method, the narrative analysis as the storytelling technique. The study uses the conceptual metaphor theory by Lakoff and Johnson (1980-1988) to justify the metaphor that tackles the characters, the actions and plot. The study has combined The Iceman Cometh and The Hairy Ape as a metaphorical study.